Engineering Structural Transitions in a Multilevel Molecular Switch via Intermolecular Coupling - Yueqing Shi; Zihao Wang; Weike Quan; Liya Bi; Kangkai Liang; Hao Zhou; Zhiyuan Yin; Wan-Lu Li; Shaowei Li (Journal of the American Chemical Society, 2026)
Abstract Controlling molecular conformations with atomic precision is essential for advancing molecular functional electronics, as well as our understanding of molecular dynamics. While switching between bistable molecular conformers is common in nature, creating systems with multiple, addressable states remains synthetically challenging. Here, we demonstrate a bottom-up strategy in which intermolecular interactions give rise to multilevel functionality within a simple two-molecule assembly. Using low-temperature scanning tunneling microscopy, we show that a pyrrolidine dimer on Cu(100) exhibits six distinct adsorption conformations, exceeding the four expected from two independent bistable units. This unusual complexity arises from the interplay between intermolecular van der Waals attraction and steric repulsion, which reshapes the potential energy landscape and changes a single high-energy transition into a sequential two-step pathway. Each step is driven by low-energy inelastic electron excitations, achieving a switching efficiency an order of magnitude higher than that of the monomer. By tuning the bias voltage and tip–molecule distance, we achieve deterministic control over multiple stable states, establishing a general design principle for on-demand engineering of collective molecular behavior and energy-efficient multilevel molecular devices.